EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI), THINK PAIR SHARE (TPS), DAN PEMBELAJARAN LANGSUNG PADA MATERI ALJABAR DITINJAU DARI KECERDASAN MAJEMUK SISWA SMP NEGERI SE-KOTA SURAKARTA TAHUN PELAJARAN 2015/2016 - Hermawati, Evi; Budiyono, Budiyono; Slamet, Isnandar (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: This research aimed to find out: 1) which one providing better mathematics learning achievement: Group Investigation (GI) Â model, Think Pair Share (TPS) model, or direct instructional model, 2) which one providing better mathematics learning achievement: linguistic intelligence students, mathematics-logic intelligence students, or interpersonal intelligence students, 3) in each type of multiple intelligences which one providing better mathematics learning achievement: GI model, TPS model, or direct instructional model, and 4) in each learning models which one providing better mathematics learning achievement: linguistic intelligence students, mathematics-logic intelligence students, or interpersonal intelligence students. This research used the quasi experimental research method. The design of the research was a 3 Ã 3 factorial. The population was the students of the seventh grade of Junior High School in Surakarta City on academic year 2015/2016. The technique of sampling was stratified cluster random sampling. The proposed hypothesis of the research were tested by the unbalanced two-way analysis of variance. The conclusions of this research were as follows. 1) GI model provided better mathematics learning achievement than TPS model, or direct instructional model; TPS model provided mathematics learning achievement as good as direct instructional model. 2) The mathematics-logic intelligence students had better mathematics learning achievement than linguistic intelligence students, or interpersonal intelligence students; the mathematics learning achievement of linguistic intelligence students as good as interpersonal intelligence students. 3) In each type of multiple intelligences, GI model provided better mathematics learning achievement than TPS model, or direct instructional model; TPS model provided mathematics learning achievement as good as direct instructional learning. 4) In each learning models, the mathematics-logic intelligence students had better mathematics learning achievement than linguistic intelligence students, or interpersonal intelligence students; the mathematics learning achievement of linguistic intelligence students as goog as interpersonal intelligence students.Keywords: Group Investigation, Think Pair Share, direct instructional learning, multiple intelligence, mathematics learning achievementÂ